Detection and eradication of Spongospora subterranea in mini-tuber production tunnels - Jessica Wright; Alison Lees; Jacquie van der Waals (South African Journal of Science, 2012)
Powdery scab, a root and tuber disease caused by the pathogen Spongospora subterranea f.sp. subterranea (Sss), poses a major problem to potato producers worldwide because it affects potato quality. Inoculum can be seed-borne or originate from contaminated growing media or contaminated equipment. During 2006, a potato mini-tuber production facility in Ceres in the Western Cape Province of South Africa had an outbreak of powdery scab. The purpose of this study was to detect Sss in the production facility and identify the source or sources of contamination so that corrective measures could be taken to eradicate the pathogen. Swab samples were taken from numerous points in the facility in 2009 and Sss-specific primers (Sps1 and Sps2) were used in a polymerase chain reaction to detect Sss. Of 11 surfaces tested, 6 were positive for Sss. A second set of swab samples was taken after efforts were made to eradicate the pathogen through improved facility hygiene measures to determine whether these corrective measures were efficient. Corrective measures resulted in a disease-free harvest from 2009 onwards. This novel study has value for the mini-tuber industry as production tunnels can be tested for the presence of Sss and other pathogens before planting to ensure that, where suitable control measures are available, disease-free mini-tubers are produced.